Investigating the rate of turbidity impact on underwater spectral reflectance detection - Song, Hong; Mehdi, Syed Raza; Li, Zixin; Wang, Mengjie; Wu, Chaopeng; Venediktov, Vladimir Yu; Huang, Hui (Frontiers in Marine Science, 2023)
Spectral reflectance detection of the targeted object is considered a vital inherent optical property for its potential to provide abundant spectral information, which is crucial in underwater spectral imaging. However, the coarse condition of the underwater environment due to turbidity causes extreme distortions in spectral reflectance detection due to the high absorption and scattering of light. To cope with the effects of light degradation on underwater spectral reflectance detection accuracy, the rate of the impacts of turbidity on spectral reflectance should be examined thoroughly. Therefore, we utilize a stare-type underwater spectral imaging system based on a liquid crystal tunable filter (LCTF) to study the effects of turbidity in underwater spectral imaging of various colored bodies. To examine the accuracy of underwater spectral reflectance detection based on escalating turbidity, the paper models the rate of increase in scattering intensity of the water body. Results show that, based on the non-linear increase in the pixel response of the black and white board, the rapid upsurge in scattering intensity occurs between 400nm to 500nm at different turbidity levels. Additionally, the spectral reconstruction of color bodies relative to the black and white board shows the maximum absolute deviation of 5.3% in spectral reflectance detection accuracy under varying turbidity. While employing underwater spectral imaging, the above findings of optimal band selection can find significant applications to improve the quality of underwater object detection.